2015
DOI: 10.1007/s00464-015-4432-2
|View full text |Cite
|
Sign up to set email alerts
|

Importance of pouch size in laparoscopic Roux-en-Y gastric bypass: a cohort study of 14,168 patients

Abstract: A smaller pouch reduces the risk of marginal ulcers, but does not predict better weight loss at 1 year. Additional stapling should be avoided as each extra centimeter increases the relative risk of marginal ulcers by 14 %.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(27 citation statements)
references
References 19 publications
1
25
0
1
Order By: Relevance
“…This points to suboptimal surgery as a risk factor for marginal ulcer [18,19], especially considering that longer stapling length more than doubled the risk for marginal ulcer at 1 year. This concurs with a recent paper on 14,168 primary LRYGB, where we demonstrated that the relative risk for marginal ulcer increased with the size of the gastric pouch (14% for each additional centimeter of stapling used for the gastric pouch [20]). These surgical factors represent important steps that the surgeon can take to reduce future complications.…”
Section: Discussionsupporting
confidence: 93%
“…This points to suboptimal surgery as a risk factor for marginal ulcer [18,19], especially considering that longer stapling length more than doubled the risk for marginal ulcer at 1 year. This concurs with a recent paper on 14,168 primary LRYGB, where we demonstrated that the relative risk for marginal ulcer increased with the size of the gastric pouch (14% for each additional centimeter of stapling used for the gastric pouch [20]). These surgical factors represent important steps that the surgeon can take to reduce future complications.…”
Section: Discussionsupporting
confidence: 93%
“…Regarding the characteristics of the surgical technique, the inferior weight loss observed in the R-RYGB group may be due to the lack of precise measurements of the stomach pouch size during revisional surgery, resulting in a larger stomach pouch [16]. However, recent study suggests that pouch size does not play a critical role in weight regain unless the pouch is very large [33]. There is also a growing evidence suggesting that the differences in the total alimentary limb length (TALL) and the length of the biliopancreatic (BPL) could play a role [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Many patients may have other work up including CT scan, right upper quadrant ultrasound, and laboratory blood work to rule out other causes of abdominal pain. In addition to 8 ruling out fistulas, stenosis, hernias, gastric pouch ulcers, and gallbladder disease, surgeons should always consider "Candy Cane Syndrome". In our experience, the classic findings for "Candy Cane Syndrome" include, an UGI filling of afferent blind limb first before "spilling" into the roux limb ( figure 2).…”
Section: Methodsmentioning
confidence: 98%
“…Patients in this series were 3 to 11 years out from their original RYGB. From the bariatric literature, we could hypothesize that after gastric bypass surgery, the gastric pouch/ blind limb could gradually enlarge from passive stretching with overeating or pouch hyperplasia (7)(8)(9) , thus causing unsatisfying weight regain, nausea, vomiting, abdominal pain and other symptoms.…”
Section: Methodsmentioning
confidence: 99%